Anti‐proliferative activity of bovine blood hydrolysates towards cancer cells in culture. (20th February 2017) - O'Sullivan, Siobhan M.; Lafarga, Tomas; Hayes, Maria; O'Brien, Nora M.
Abstract: Four proteins, α/β globulin, serum albumin, γ‐globulin and fibrinogen, were isolated from bovine blood and hydrolysed using papain. Hydrolysates were assessed for non‐cellular and cellular antioxidant activity. The anti‐proliferative activity of hydrolysed fractions was assessed in a number of cancer cell lines including U937 lymphoma cells, MCF‐7 breast cancer cells, HepG2 hepatocytes and Caco‐2 epithelial colorectal adenocarcinoma cells. Anti‐inflammatory activity of the hydrolysates was also assessed. Hydrolysates generated from γ‐globulin or fibrinogen had significant antioxidant activity in non‐cellular assays. Hydrolysates were also found to be highly toxic to different cancer cell lines, in particular U937 lymphoma cells when assessed using the MTT assay. The fibrinogen hydrolysate was the most toxic sample and toxicity appeared to correlate with its non‐cellular antioxidant activity. None of the hydrolysates had significant anti‐inflammatory activity. The high cytotoxicity of the γ‐globulin and the fibrinogen hydrolysates towards cancer cells may indicate a potential use as anti‐proliferative agents. Abstract : Four bovine blood proteins were hydrolysed using papain to produce hydrolysates which were assessed for bioactivity in cells.